Access Programs for Health and Social Services in the English Language : Presentation to NPIs - Prata, Ghislaine (2019)

Baseline Data Report 2018-2019 Part 1 (Telephone Survey) : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network, 2019)
The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2018-2019 explores a single factor that is a key determinant of the health of English-speaking Quebec, namely, access to health and social services.

Baseline Data Report 2018-2019 Part 2 (Focus Groups) : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network, 2019)
The CHSSN focus groups were designed as face-to-face group discussions with a lead moderator. As the accompanying table indicates, nine focus groups were held across six regions with a total attendance of 116 English speakers (18+). The recruitment process entailed a public announcement by the host organizations located in each region: Neighbours Regional Association of Rouyn-Noranda (NRARN), English Community Organization in Saguenay-Lac-St-Jean (ECO-02), North Shore Community Association (NSCA), Coasters Association (Coasters), Megantic Community Development Corporation (MCDC), and the Centre for Access to Services in English (CASE). The host organizations in each region also assumed responsibility for arranging a time, finding a location, providing refreshments and technical assistance.

English-speaking Quebecers Shows High Levels of Distrust with Coalition Avenir Québec Government - Quebec Community Groups Network (QCGN) (2019)

Annual Report 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)

August 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 6

English-speaking fathers in Quebec exposed to greater vulnerability - Community Health and Social Services Network (CHSSN) (2019)

June 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 7

May 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 5

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 6

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 8

QCGN Begs to Differ on Premier's Interpretation of English Signage in Hospitals - Quebec Community Groups Network (QCGN) (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 6

Survey on Access to Health Care and Social Services for the English-speaking Community of Laval - AGAPE (2019)

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)
Number of pages: 6

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)
Number of pages: 6

Vitality - Community Health and Social Services Network (CHSSN) (2019)
Keywords: Official Language Minority Community (OLMC)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

Who Are Our 0-5 year Olds? : A Portrait of English-speaking 0-5 Year Olds in the Outaouais Region WHO AREOER - Connexions Resource Centre (2019)

Community Mobilization Model for Improving the Health and Vitality of English-Speaking Communities in Quebec - Kueber, Russell (Community Health and Social Services Network (CHSSN), 2019)
This brief description of a "Community Mobilization Model for Improving the Health and Vitality of English-speaking Communities in Quebec" includes a condensed background of English-speaking communities. It also includes a short description of some key concepts used in the model. The model is designed to communicate the approach taken by community helath and social services networks, which positions them as drivers of change in mobilizing English-speaking communities.

Promoting the Health and Well-being of English Speaking Seniors in Quebec : A Community Model - Kueber, Russell; Pocock, Joanne; Hobbs-Robert, Jennifer; Hale, Jeffery (Community Health and Social Services Network (CHSSN), 2019)
This document describes a community model for improving the health and well-being of a linguistic minority senior population in Quebec. English-speaking seniors have unique challenges due to language barriers, socioeconomic inequalities as well as the lack of awareness of their needs and lack of representation associated with the minority status of their community. Many community organizations have recognized the critical level of vulnerability of this population and have designed and implemented successful strategies to address these challenges while remaining aligned with the Quebec government's comprehensive strategies and approaches on healthy aging such as Vieillir et vivre ensemble and Municipalite amie des aines. The main purpose of the document is to help inform and guide English-speaking communities and their community and public partners in their ongoing collaborative efforts to effectively adapt programs and services to improve the lives of English-speaking seniors in their communities.